Nicholas of Cusa’s Mystical Theology in Jean-Luc Marion’s Phenomenology of Affectivity - Pizzi, Matías Ignacio (2022)
The main goal of this paper is to analyze Nicholas of Cusa´s reading on the dispute of mystical theology through Jean-Luc Marion´s phenomenology of givenness. To do this, first of all, we will address the analyses offered by Jean-Luc Marion on the problem of affectivity. Secondly, we examine Nicholas´ interpretation of mystical theology through the aenigma of the eicona dei in De visione dei (1453). Thirdly, we present Jean-Luc Marion´s interpretation of Cusanus eicona dei as an antecedent of his phenomenological conception of Icone as ?saturated phenomenon.? Finally, we suggest that Cusanus eicona dei appears in Jean-Luc Marion´s phenomenology as a precedent of his strategy when approaching the field of affectivity. Both authors try to show an instance preceding the distinction between affectivity and rationality.